Psychiatric Dispositive and Production of Killable Subjects in Brazil between the Late 19th and Early 20th Centuries - Soares, Silvio de Azevedo (2019)
From Michel Foucault’s contributions (and his concepts of biopower and dispositive) and Giorgio Agamben (Homo Sacer) it is discussed how deaths were produced by the psychiatry in Brazil of the late nineteenth and early twentieth century. Through bibliographic review in works dealing with psychiatry in this historical period, the article analyzes, in interpretations of psychiatric discourses and practices, the implication of biological characteristics, aspects of the bare life of individuals and groups, which would turn them into killable subjects, close to the condition of Homo Sacer, and exposed to death within the psychiatric weft.